Prevalence of HCV Infection in End Stage Renal Disease (ESRD) Patients on Maintenance Hemodialysis: HCV Infection in End Stage Renal Disease - Kumar, Kishor; Das, Bhagwan; Naveed, Asma; Kumar, Santosh; Tassaduq Khan, Muhammad; Memon, Rafia (Pakistan Journal of Health Sciences, 2023)
Hepatitis C virus (HCV) is a significant cause of morbidity and mortality in haemodialysis patients. Patients on haemodialysis are at high risk for HCV, with frequency of infection several times higher than that in non-hemodialysis patients. Objective: To determine the frequency of HCV infection in End Stage Renal Disease (ESRD) patients on maintenance hemodialysis. Methods: The Descriptive Cross-sectional study was conducted at Department of Nephrology, Liaquat University of Medical and Health Sciences Jamshoro. All patients above 18 years of age and below 60 years of age of both gender having end stage renal disease on maintenance hemodialysis with 3 months or more of maintenance hemodialysis were consecutively enrolled. Post hemodialysis patient’s serum was checked for anti HCV antibody by enzyme linked immune-sorbent assay (ELISA). Presence of anti HCV antibodies in serum detected by ELISA was labeled as HCV positive. Results: Of 90 patients, the mean age of the patients was 46.85 ±8.21 years. There were 54 (60%) males and 36 (40%) females. The mean duration of hemodialysis was 10.39 ±3.31 months. The frequency of HCV was found to be 21 (23.3%). A significant association of HCV was found with gender (p-value 0.006) whereas age (p-value 0.597) and duration of hemodialysis (p-value 0.715) was found to be insignificant. Conclusion: The frequency of HCV infection was found to be 23% in ESRD patients on maintenance hemodialysis. Early recognition and treatment of which improves the patient outcome.